Fungos Amazônicos com potencial para degradação de Polietileno da Amazônia - Soares, Elaine Pires (2012)
This work aims to study the degradative action of the synthetic polymer polyethylene terephthalate - PET by basidiomycetous fungi Amazon. Three different fungal strains (P. sanguineus, FBL, FV12) and the consortium between them in stationary liquid culture medium, with or without supplementation with flour bark tucumã at 15, 30, 60 and 90 days of growth at 27 ° C +1. Samples of PET were subjected to pre-treatment temperature 35 ° C and 50 ° C. After incubation were evaluated polymer mass loss, the determination of ligninolytic enzymes and analysis of samples using PET scanning electron microscopy to verify the occurrence of morphological and / or structural polymeric surface. All the strains resulted in loss of mass of PET, the highlights were the fungi FBL and FV12 and the consortium C1-PYC + FBL + FV12 within 90 days of cultivation, with PET subjected to the pretreatment temperature 50 ° C, with greater weight loss plastic. All fungi tested showed enzyme activity lignolítica. The manganese peroxidase (MnP) was the enzyme that showed the highest activity among the three enzymes studied. The strain FV12 PET subjected to temperature 50 ° C in 90 days of incubation showed the highest mean value of this enzyme. It should be noted that the best results were obtained with a culture medium supplemented with tucumã shell flour. shows that PET subjected to temperature 50 ° C, suffered severe wear of the polymeric surface with flaking, ruptures and cracked appearance across the surface, as well as bleaching of the sample. It follows that the Amazon fungi studied have potential to degrade the Polyethylene Terephthalate. Keywords: Fungi Amazon, Polyethylene Terephthalate, oxidative enzymes, biodegradation.